The causal effect of triglyceride and high blood pressure on IgA nephropathy: a Mendelian randomization study - Yang, Yijun; Li, Yang; Feng, Xinshun; Ding, Chenguang; Zhang, Jing; Liu, Zunwei (Frontiers in Medicine, 2024)
Background: It has been reported that high blood pressure (HBP) and triglyceride (TG) are considered risk factors in immunoglobulin A nephropathy (IgAN). This study aimed to explore the causalities between HBP and TG, and IgAN on the basis of Mendelian randomization (MR) analysis.Methods: Firstly, the genome-wide association study (GWAS) summary data of IgAN (GCST90018866) and two exposure factors, TG (ukb-d-30870_raw) and HBP (ukb-a-437), were sourced from the GWAS Catalog and Integrative Epidemiology Unit (IEU) OpenGWAS databases, respectively. In this stugy, five methods were utilized to perform MR analysis after picking out single nucleotide polymorphisms (SNPs) as instrumental variables, including MR-Egger, Weighted median, Simple mode, Weighted mode, and Inverse variance weighted (IVW), followed by the sensitivity analysis containing the Heterogeneity, Horizontal pleiotropy test and Leave-One-Out (LOO) analysis. Finally, the enrichment analysis and interaction network construction of genes corresponding to SNPs of HBP and TG were performed.The univariate MR results revealed that HBP and TG regarded as risk factors were causally related to IgAN (TG: P=0.046, odds ratio (OR)=1.065, 95% confidence interval (CI)=1.001-1.133; HBP: P=7.09×10-7, OR=1.970, 95% CI=1.507-2.575) based on random-effect IVM method, of which TG had a weaker impact. The reliability of these univariate MR results was certified by the sensitivity analysis, in which there was no horizontal pleiotropy and exaggerated influence of each SNP. Furthermore, HBP was markedly causally related to IgAN (P=0.000512) with the help of multivariate MR analysis, rather than TG (P=0.332). Therefore, when HBP and TG occur simultaneously, HBP is a direct influencing factor on IgAN. Ultimately, a total of 208 and 153 genes separately corresponding to SNPs of TG and HBP were included in enrichment analysis, and thereinto, genes relevant to TG were mainly enriched in lipid homeostasis and cholesterol metabolism, while genes concerned with HBP played their roles in regulation of cell growth, aldosterone synthesis and secretion and so forth.TG and HBP as risk factors were causally connected with IgAN, of which HBP was strongly related to the onset of IgAN, providing more reliable evidence for further exploring the relationship between TG and HBP and IgAN.